Crusading and archaeology (London ; New York)
xxiv, 407 sayfa
Keywords: “Between the eleventh and fifteenth centuries, the social and cultural worlds of medieval Europe and the Eastern Mediterranean were transformed by the religious impetus of the crusades. Today we bear witness to these transformations in the material and environmental record revealed by new archaeological excavations and reappraisals of museum collections. This volume highlights new archaeological knowledge being developed by scholars working in the fields of history, archaeology, numismatics, and architecture to demonstrate its potential to change and augment our understanding of the crusades. The 16 chapters in this volume deploy a contemporary scientific approach to archaeology of the crusades to give an up-to-date account into the diverse range of research in this area. They explore five key themes: the implications of scientific methods, new excavations and surveys, architectural analyses, sigillography, and the application of social interpretations. Together these chapters provide a new way of approaching the study of the crusades, and demonstrate the value of taking a holistic view that utilises the full diverse range of evidence available to us.” --